PSIKOEDUKASI PENDIDIKAN SEKS KEPADA GURU DAN SISWA SEBAGAI UPAYA PENCEGAHAN KEKERASAN SEKSUAL PADA SISWA SD - Fitriatul Masruroh; Ellyana Ilsan Eka Putri; Fathi Hidayah; Riza Faishol (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
Community service on the socialization of sex education to teachers and students to improve understanding and skills related to sexual violence in children as an effort to prevent sexual violence against children. This service is also motivated by the results of cases of sexual abuse in children which are increasing every year so that prevention is needed through psychoeducation of sex in children. The method used in this service is mentoring and training which consists of three stages, namely preparation, implementation and monev. After this service program, the ability of teachers and students to demonstrate that sex education can increase teacher and student understanding of sexual violence.